Measuring and Mapping Social Capital Through Assessment of Collective Action to Protect the Irrigation in Lakbok Sub-District, Ciamis Regency, Province of West Java, Indonesia - Setiawan, Tomi; Sintaningrum, Sintaningrum; Nurasa, Heru (Journal of Rural Indonesia [JORI], 2015)
Social capital is a popular concept in the literature of development, and development agencies at this time. This study examines the relationship between measures of social capital with the protection of irrigation in five villages in Lakbok sub-district, Ciamis Regency, by taking research focused on the village which has the largest irrigated rice fields. The data collection includes literature survey, site survey, as well as interviews and fill out questionnaires on selected respondents in five villages evenly distributed either sex male or female, then do also five sessions focus group discussions (FGDs) with village leaders and elected representatives, as well as the data obtained from the relevant village official monograph documents the village. Then con- ducted data analysis of quantitative and qualitative (mixed method). The result, social capital owned five villages in Lakbok Sub-district in general has been corrupted. afterwards, in measures of social capital for the protection of irrigation, there are similarities and differences in the results for one village to another. villagers do not actively participate in the protection of irrigation. The capacity of social capital such as the activity of the community, tolerance, and religious values are strong not fully utilized for the protection and management of irrigation.Keywords: mapping social capital, collective action, management of irrigation